Transcatheter embolization of a pulmonary collateral vessel in a child with tricuspid atresia - Karaaslan, Sevim; Çeliker, Alpay; Günal, Nazlıhan (The Turkish Journal of Pediatrics, 1996)
When a significant systemic-pulmonary arterial collateral connection occurs in children with cyanotic congenital heart disease, they may present surgical difficulties making operative management undesirable. Transcatheter vessel occlusion can be a life-saving procedure or an important adjunct in reducing blood loss during surgery. This report describes the selective obliteration of a large systemic pulmonary arterial collateral vessel in a child with tricuspid atresia before Fontan operation. A transcatheter wire coil embolus technique was used, and no complications or errors in placement of the coils occurred.